Compósitos híbridos: desenvolvimento de configuração e efeitos de umidificação - Barros, Alysson Régis de Freitas (2006)
The advantage in using vegetable fibres in place of synthetic fibres such as glass fibre, for reinforcements in composites are: biodegradability, low cost, low density, good tenacity, good thermal properties, low energy content and reduced use of instruments for its treatment or processing. Even though, problems related to low mechanical performance of some of the natural fibres, has caused difficulty in their direct application in structural elements. The use of alternative materials like hybrid composites has been encouraged, thus trying to better the structural performance of the composites with natural fibres. This work presents a comparative study of the strength and stiffness of hybrid composites with orthopthalic polyester matrix reinforced with E-fibre glass, jute and curauá. The experimental part includes uniaxial tension and three point bending tests to determine the mechanical properties of the final product. The hybrid composite was manufactured in a local industry and was in the form of laminates. All the samples were projected to withstand the possible structural applications as reservoirs and pipes. CH (laminated hybrid composite with glass and curauá fibres). The results obtained show clearly the influence of the hybridization in all the types tested and indicate a good mechanical performance of the composite with glass/curauá fibres in relation to the composite with glass fibres. Aspects in relation to the interfaces glass/curauá composites besides the fracture characteristics for all loading types were also analysed